Association of serum uric acid with all‐cause and cardiovascular mortality among adults with nonalcoholic fatty liver disease. (22nd August 2022) - Yang, Sisi; Ye, Ziliang; Liu, Mengyi; Zhang, Yanjun; Wu, Qimeng; Zhou, Chun; Zhang, Zhuxian; He, Panpan; Zhang, Yuanyuan; Li, Huan; Liu, Chengzhang; Qin, Xianhui
Abstract: Aim: The association between serum uric acid (SUA) and mortality from cardiovascular diseases (CVDs) in nonalcoholic fatty liver disease (NAFLD) participants remains uncertain. We aim to investigate the relations of SUA with the risk of CVD mortality among adults with and without NAFLD. Methods: Using data from National Health and Nutrition Examination Survey (NHANES) 1999–2014, a total of 17, 858 participants were recruited. Of these, 5767 had a US Fatty Liver Index (USFLI) ≥30 and were classified as having NAFLD. Death information was obtained from the National Death Index until 2015. Results: During a mean follow‐up of 8.3 years, 427 participants died from CVD. Overall, there was a positive association between SUA and CVD mortality among participants with NAFLD (per SD μmol/L increment, adjusted hazard ratio [HR], 1.40; 95% confidence interval [CI], 1.16–1.68). Accordingly, among those with NAFLD, when SUA was assessed as quartiles, compared with those in the first quartile, a significantly higher risk of CVD mortality was found in participants in the fourth quartile (adjusted HR, 2.69; 95% CI, 1.51–4.80). However, there was no significant association between SUA and CVD mortality among participants without NAFLD (per SD μmol/L increment, adjusted HR, 1.01; 95% CI, 0.83–1.22). Similar trends were found for all‐cause mortality. Similar results were also found when using FLI ≥ 60 to define NAFLD. Conclusions: In a large and nationally representative sample of US adults, a higher SUA was significantly associated with a higher risk of CVD mortality among participants with NAFLD, but not in those without NAFLD.